‘Urf Tentang Jual Beli Mu’athoh Perspektif Hukum Ekonomi Syariah (Studi Kasus di Mini Market Najma Mart Lombok Timur) - Musannif, Musannif; Latifah, Luluk; Suadi, Amran (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the practice of mu'athoh buying and selling at the Najma Mart Mini Market in East Lombok from the perspective of Islamic economic law. The background of this research is based on the phenomenon of transactions without verbal consent, but rather through direct actions such as the delivery of goods and payment. This practice is common in modern markets, but continues to generate debate regarding its legal validity in Islamic transactions. The purpose of this study is to analyze the implementation of mu'athoh buying and selling at Najma Mart, understand the underlying 'urf (community customs), and assess its compliance with the principles of Islamic economic law. The research uses a qualitative method with a case study approach, through observation, interviews with managers and customers, and document review. The results of the discussion indicate that the practice of mu'athoh buying and selling at Najma Mart has become a 'urf sahih' (authentic) accepted by the community. Transactions using a self-service system and payment at the cashier are considered valid by the majority of contemporary Islamic jurisprudence scholars, as long as the elements of object clarity are met and there are no elements of gharar or fraud. These findings confirm that Islamic law is flexible and contextual, able to adapt to modern economic developments without abandoning the values ​​of justice and transparency. Consequently, an understanding of muamalah law needs to consider social changes to remain relevant in contemporary economic practices.